The Role of Song as a Media to Improve English Vocabulary on Teenagers - Wulandari, Rifa Suci; Putri, Ananda Reka; Widyawati, Wiwin (STKIP PGRI Ponorogo Press, 2024)
Vocabulary is important in every language. By using vocabulary, we can easily exchange information with others. Similarly, English as an international language also has a lot of vocabulary. In the current era of globalization, there are many ways to improve English vocabulary. Many media that can be used, ranging from social media, applications, songs, etc. Media is something that can be used to facilitate someone in learning. Learning can be done independently, one of which is using song. This research focuses on improving English vocabulary on teenagers through English songs. It aims to describe the use of English songs as a media to improve English vocabulary on teenagers. This study was a qualitative descriptive. The technique of collecting data used questionnaire. The subjects of this study were male and female teenagers aged 11-21 years. After distributing the questionnaires randomly by fulfilling the respondents’ criteria, 37 teenagers were obtained who voluntarily filled out the questionnaires. The results of the study show that English songs have an important role in improving teenagers’ English vocabulary and can be used effectively as a medium to improve English vocabulary on teenagers.